Pakistani Women’s Dignity in Patriarchal Culture Reflected in Qaisra Shahraz’s A Pair of Jeans and Other Stories - Indri Octarinanda; Seswita Seswita (English Department, Faculty of Humanities, Andalas University, 2020)
This article discusses the problems faced by women and their dignity to survive in the domination of a patriarchal cultural environment. This study uses prescriptive criticism from Cheri Register to analyze three short stories by Qaisra Shahraz entitled Zemindar’s Wife, A Pair of Jeans and The Elopement. The concept of prescriptive criticism from Cheri Register has four criteria that supposed to be found in literary works, namely serves as a forum for women, helps to achieve cultural androgyny, provides role-models, promotes health and augment consciousness-raising systems. The results showed that the main female characters; Noor, Miriam and Rubiya can survive in the dominant patriarchal culture with the dignity to resist in the patriarchal culture. These three stories successfully covered four prescriptive criteria by Register and can be classified as feminist stories.